Reset : how to change what's not working - Heath, Dan
"From the #1 New York Times bestselling coauthor of Made to Stick, Switch, and The Power of Moments comes a revolutionary guide to fixing what's not working-in systems and processes, organizations and companies, and even in our daily lives-by identifying leverage points and concentrating resources to achieve our goals"-- Provided by publisher.
LC copy bound upside down.
Includes bibliographical references (pages 239-251) and index.
Keywords: Organizational change; Organizational effectiveness; Workflow; Labor productivity